Lipid Oxidation Assessed by Indirect Calorimetry Predicts Metabolic Syndrome and Type 2 Diabetes - Pujia, Arturo; Mazza, Elisa; Ferro, Yvelise; Gazzaruso, Carmine; Coppola, Adriana; Doldo, Patrizia; Grembiale, Rosa Daniela; Pujia, Roberta; Romeo, Stefano; Montalcini, Tiziana (Frontiers in Endocrinology, 2019)
Purpose: Diabetes has been linked to an impaired ability to oxidize fatty acids. Fat oxidation can be assessed clinically by a respiratory quotient measurement during fasting. We hypothesized that a respiratory quotient might predict metabolic syndrome and type 2 diabetes onset. Methods: In this longitudinal study we used an existing database of 233 individuals who had complete nutritional and biochemical data at baseline and after 12-month follow-up. All participants underwent an indirect calorimetry to measure the respiratory quotient. We excluded participants with diabetes, metabolic syndrome, chronic diseases, and those who had changed food habits in the previous 3 months. Only 88 subjects met the inclusion criteria. Results: Two individuals developed type 2 diabetes and 10 metabolic syndrome after 1 year. Participants in the high respiratory quotient group (>0.91) had a higher incidence of metabolic syndrome/diabetes than those in the low quotient group (25 vs. 8% p = 0.04). In this group, mean basal respiratory quotient was 0.97 ± 0.04. In the high respiratory quotient group, Kaplan-Meier curves showed a greater probability of having metabolic syndrome/diabetes than those in the low respiratoryquotient group (log Rank χ2-test = 8.44; p = 0.004). A multivariable Cox proportional hazards model demonstrated that energy expenditure and weight increase did not predict metabolic syndrome/diabetes [HR (95% CI) = 1 (0.996–1.005), p = 0.86 and 3.9 (0.407–38.061), p = 0.23, respectively). Conclusions: A greater probability of metabolic syndrome/diabetes was found in individuals with a basal respiratory quotient of >0.91 than in those with a respiratoryquotient of ≤ 0.91 after 1 year. In the short-term anthropometric measurements and their variation overtime were not correlated with metabolic syndrome/diabetes.